Thermoplastic hydrogel elastomer composites through compatibilization with common copolymer end blocks - Morris, William Boston, author; Bailey, Travis S., advisor; Herrera-Alonso, Margarita, committee member; Prawel, David, committee member; Dandy, David, committee member (Colorado State University. Libraries, 2025)
The development of immiscible polymer-polymer composites that unify disparate material properties into a single bulk material has long been hindered by challenges in stabilizing incompatible polymer domains against macrophase separation while achieving sufficient interfacial adhesion for efficient mechanical load transfer. This work introduces a new class of polymer-polymer composites designed to address these challenges based on forming composites between styrenic block copolymer (SBC) thermoplastic elastomers (TPEs) containing immiscible copolymer midblocks with distinct material characteristics. Leveraging the inherent microphase separation behavior of ABA block copolymer systems, which are widely used in TPEs to generate reversible physical crosslinking, this work establishes a simple, scalable, and tunable method for fabricating tough, durable, and intrinsically lubricious hydrogel-elastomer composites; soft, elastic, hydrophilic hydrogel-silicone composites; and porous, hydrophilic elastomers. By combining TPE materials that share common vitreous polystyrene end blocks, each component forms its own phase-separated elastomeric network while simultaneously experiencing enhanced interfacial adhesion. Continuous vitreous domains formed at the component interfaces stabilize the blend morphology and enable mechanical load transfer between phases. Adjusting the compositional ratios and specific TPEs selected allow this composite platform to be tailored to meet a diverse range of performance specifications pertinent in medical devices, soft electronics, and membrane technologies. The thermoplastic hydrogel-elastomer and hydrogel-silicone composites developed in this work specifically address the persistent need for intrinsically lubricious, low-friction polydiene-based elastomers and silicones. Traditional elastomers, while flexible and durable, often suffer from tacky surfaces that require secondary lubricious treatments for medical device applications. Conversely, hydrogels offer excellent lubricity and poroelastic relaxation but typically lack scalable methods for introducing the needed mechanical strength and toughness. By integrating an SBC thermoplastic hydrogel phase into either commercial SBC TPEs or a newly developed PDMS-based SBC TPE, this work demonstrates the creation of versatile hydrogel composites featuring hydrophilic lubricious surfaces and outstanding mechanical durability while remaining thermally processable using standard processing techniques such as injection molding and extrusion, without the use of fluoropolymers. Their commercial application in minimally invasive intravascular catheter componentry was specifically explored through NSF's National I-Corps Program. Finally, by applying the same compatibilization strategy, a novel and straightforward method was developed for generating porosity into TPEs while simultaneously introducing a dense, uniform hydrophilic PEO brush layer conformally coating all internal pore surfaces. The mechanical viability of these porous elastomers towards potential membrane applications is examined.
Keywords: composite; hydrogel; thermoplastic; elastomer; compatibilization; polymer